Mangrove diversity and structure of Karimunjawa National Park, Indonesia: Conserving forest patches in small island ecosystem - MUHAMMAD ARIF ASADI; ALIFYA NADHIRA JASMINE; ANNAS TASYA WIDODO; ANDIK ISDIANTO; RIZKY RAFINALDO; HILMAN FAKHRUR ROZI; MUH FIRDAUS (Society for Indonesian Biodiversity, 2025)
Abstract. Asadi MA, Jasmine AN, Widodo AT, Isdianto A, Rafinaldo R, Rozi HF, Firdaus M. 2025. Mangrove diversity and structure of Karimunjawa National Park, Indonesia: Conserving forest patches in small island ecosystem. Biodiversitas 26: 5350-5359. Mangrove forests are vital coastal ecosystems, and in small island settings their conservation requires more attention including continuous assessment. This study investigated the diversity and structural characteristics of mangroves in Karimunjawa National Park (KNP), Indonesia, across zones and forest patches to extend beyond previous research. Field surveys in 39 plots (10 m × 10 m) across 13 locations on Karimunjawa and Kemujan Islands recorded 1,065 individuals from 15 species in eight families. Species density ranged from 5.13 ind./ha (Heritiera littoralis) to 1,230.77 ind./ha (Ceriops tagal), while basal area varied from 0.05 m²/ha (Bruguiera gymnorhiza) to 4.95 m²/ha (Rhizophora apiculata). Ceriops tagal had the highest importance value, followed by R. apiculata, Excoecaria agallocha, and Lumnitzera racemosa. Ecological indices showed moderate species diversity (Shannon–Wiener H’ = 1.73), relatively even distribution (Pielou’s J = 0.64), and low dominance (Simpson’s C = 0.26), indicating a mature and structurally balanced forest, although the community composition reflects dominance by a few key species with lower representation of rare taxa. The relatively high density of dominant species suggests successful regeneration yet highlights potential vulnerability if disturbances disproportionately affect these taxa. Mangroves in small islands setting in KNP are limited in area and highly sensitive to human pressures such as aquaculture and tourism. Safeguarding them is essential for ecosystem services and local livelihoods. Our findings provide baseline data to guide monitoring, zoning, and rare species protection, underscoring the need for integrated management to ensure long-term resilience.